Kajian tentang tadbir urus dan risiko dalam perhubungan terhadap perkongsian maklumat di kalangan pengusaha stesen minyak luar bandar di Malaysia - Azizi, Romli (2019)
One of the New Economic Policy (NEP) is to increase rural development and to bridge the economic gap between the urban and rural areas. The importance of the rural petroleum retailing industry in supplying fuel sources is the driving force for economic activity in the rural areas in Malaysia. Issues concerning the rural oil supply chain in Malaysia needs to be addressed effectively and efficiently to ensure timely supply. Practicing information sharing between suppliers and retailers is a critical process to ensure alignment in the supply chain management. To address the issue of information sharing in the supply chain, a research framework was developed to delineate the relationship between relational governance and information sharing through the role of mediating relational risk. The testing of research framework was conducted using the questionnaire which 162 questionnaires were distributed to rural petrol station operators in Malaysia. Of these, only 65 questionnaires were returned and could be used for the data analysis phase. The data were analyzed using descriptive statistical approaches and inferential statistics. The findings show that the level of information sharing is at a moderate pace. Meanwhile, relational governance is a simple predictor of information sharing but has an influence on information sharing through relational risk mediator. This demonstrates the need for relational governance to focus on relational risk issues in order to contribute to information sharing. Findings also showed that relational risk acts as partial mediator between relational governance and information sharing with significant influence. Relational governance dimensions of connectedness, can be the catalyst for improved information sharing performance. The results of this study are expected to contribute towards the proliferation of knowledge - related information sharing in the supply chain to the academic and industry players in implementing supply chain management more efficiently and effectively through information sharing.